If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(a + 3) = 2a + -12 Reorder the terms: 4(3 + a) = 2a + -12 (3 * 4 + a * 4) = 2a + -12 (12 + 4a) = 2a + -12 Reorder the terms: 12 + 4a = -12 + 2a Solving 12 + 4a = -12 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 12 + 4a + -2a = -12 + 2a + -2a Combine like terms: 4a + -2a = 2a 12 + 2a = -12 + 2a + -2a Combine like terms: 2a + -2a = 0 12 + 2a = -12 + 0 12 + 2a = -12 Add '-12' to each side of the equation. 12 + -12 + 2a = -12 + -12 Combine like terms: 12 + -12 = 0 0 + 2a = -12 + -12 2a = -12 + -12 Combine like terms: -12 + -12 = -24 2a = -24 Divide each side by '2'. a = -12 Simplifying a = -12
| -25d+2s-7+15s-20d= | | -11a^2b*8ab= | | 7x+14-2x-5=3x | | 7x+14-2x-5=3x | | 5a*a^2= | | 2(x+6)=9x+9-7x+3 | | 3a^2-3a= | | 20j+20j-16m-16m+16= | | 6k-(4k+2)-8+8(2k+2)=0 | | x-5=28 | | 6k-(2k+2)-8+8(2k+2)=10 | | 6k-(4k+2)-8+8(2k+2)=10 | | 10+(-4g)+10-13x-2g+5x= | | 2.75=f-.25 | | 3x-15+10x=13x+20 | | 5y+7=1-7y | | -19m+5-(-m)+c-7c= | | 7x-4+3x+12= | | 7x-4+3x+12=30 | | 3x+(-17)+21f+3x-(-21f)= | | 3y-20+y+40=120 | | 3y-20+y+40=180 | | 3y-20+y+40=90 | | 3y-20+y+40=30 | | 3x-20+x+10=30 | | 3(3m-4)-(2m-3)=m+9 | | 3x-20+x+10=90 | | 3x-20+x+10= | | 2(-1)+1= | | 6k-4k=6 | | 7t-14-16t+9c+(-14c)= | | 5x-10+3x+40=30 |